Upaya Guru Mengatasi Kesulitan Peserta Didik Kelas VI dalam Membaca Al-Qur’an di SDIT Al-Maqom Cimahi - Putri Tatim Aulia; A. Mujahid Rasyid; Dinar Nur Inten (Bandung Conference Series: Islamic Education, 2022)
Abstract. Many parents want their children's education to be better, especially in the field of Islam, one of which is in terms of reading the Qur'an, many parents choose to send their children to Islamic-based schools, entrust their children to school and entrust their children's education to schools such as in SDIT Al-Maqom Cimahi where the storefront is a school but inside is a boarding school, so that children get more education in the field of Islam. Based on the results of a survey in the field regarding the ability to read the Qur'an of class VI students, there are 25% or 14 students out of 55 students who are still having difficulties. The purpose of the study was to determine the efforts of religious teachers to overcome the difficulties of class VI students at SDIT Al-Maqom Cimahi in reading the Qur'an. The approach used in this study is a qualitative research approach with descriptive methods, data sources obtained from primary and secondary data and data collection techniques through interviews, observations and questionnaires. The results of the discussion discuss the difficulties experienced by students in reading the Qur'an, namely in understanding the hijaiyah letter, the difficulty in understanding the hijaiyah letter and the difficulty in understanding recitation. Then the factors that affect students' difficulties in reading the Qur'an are because of the students' internal factors. Then external factors, from the school environment and environmental factors of friends. Efforts that can be made to overcome the difficulties of SDIT Al-Maqom students in reading the Qur'an are carried out by schools and grade VI teachers of SDIT Al-Maqom. Abstrak. Banyak orang tua yang menginginkan pendidikan anaknya lebih baik terutama dalam bidang agama Islam, salah satunya yaitu dalam hal membaca Al-Qur’an, banyak orang tua memilih memasukkan anaknya di sekolah yang berbasis Islami, mempercayakan anaknya disekolah dan menitipkan pendidikan anaknya kepada sekolah seperti di SDIT Al-Maqom Cimahi dimana etalasenya adalah sekolah namun di dalamnya pesantren, dengan begitu anak memperoleh banyak pendidikan bidang agama Islam lebih banyak. Berdasarkan hasil survey di lapangan terkait kemampuan membaca Al-Qur’an peserta didik kelas VI terdapat 25% atau 14 peserta didik dari 55 siswa yang masih mengalami kesulitan. Tujuan penelitian untuk mengetahui upaya guru agama yang dilakukan dalam mengatasi kesulitan peserta didik kelas VI SDIT Al-Maqom Cimahi dalam membaca Al-Qur’an. Pendekatan yang digunakan dalam penelitian ini yaitu pendekatan penelitian kualitatif dengan metode deskriptif, sumber data diperoleh dari data primer dan sekunder dan teknik pengambilan data melalui wawancara, observasi dan angket. Hasil pembahasan membahas kesulitan yang dialami siswa dalam membaca Al-Qur’an yaitu dalam pemahaman huruf hijaiyah kesulitan pemahaman huruf hijaiyah Dan kesulitan dalam pemahaman tajwid. Lalu faktor yang mempengaruhi siswa kesulitan dalam membaca Al-Qur’an yaitu karena faktor internal diri siswa. Lalu faktor eksternal, dari lingkungan sekolah dan faktor lingkungan teman. Upaya yang dapat dilakukan untuk mengatasi kesulitan siswa SDIT Al-Maqom dalam membaca Al-Qur’an dilakukan oleh sekolah dan guru kelas VI SDIT Al-Maqom.